Russian scientometrics: a review of researches - A. E. Guskov (Библиосфера)
The article provides an overview of scientometric researches made by Russian scientists in 2000-2014. It considers a number of papers on the state, dynamics and spheres of the Russian science specialization, international cooperation of Russian scientists, aspects of using scientometric indicators and databases. The problem of Russian publications low citation abroad is highlighted. The most cited bibliographic reviews in various fields of science are listed: medicine, chemistry, physics, nanotechnology, sociology, ethnography and others. The review results can be used to discover directions of further development and to form new topics of scientometric studies.